Prognozowanie zmienności kursów walutowych na podstawie przełącznikowych modeli Markowa - Włodarczyk, Aneta (Forecasting exchange rate volatility on the basis of Markov switching models, 2006)
The exchange rate volatility determines investment decisions of market participants. The main purpose of this paper is an application of Markov switching models to forecasting the exchange rate volatility in the Polish currency market. Switching models describe dynamics of processes that are subject to discrete changes with time and it is assumed that the regime change mechanism is random. In Markov switching models, the stochastic process that controls the regime changes is a homogeneous Markov chain. The volatility forecasts are the forecasts of the variance of the exchange rate change over a h-day horizon (h = 1, h = 10, h = 21). The important implication of using Markov switching models for volatility forecasting is that the conditional variance is a function of smoothed regime probabilities. Some statistical criteria are used to investigate the forecasting performance of Markov switching models.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 567-574